SUICIDE AND THE SOCIAL SECURITY EARLY RETIREMENT AGE. (13th February 2017) - DeSimone, Jeffrey
Abstract : Using a regression discontinuity framework, this paper documents a previously unnoticed drop of 7%–8% in the U.S. suicide rate upon reaching age 62 during 1990–2014. This decline is concentrated among men, nearly doubled in size over the most recent decade as the income gap between those just older and younger narrowed, and represents the only trend break among ages 45–79. These findings, along with the observed timing of retirement and benefit claims and research on how income affects suicide, suggest that the likely explanation is Social Security early retirement benefit eligibility rather than retirement per se. ( JEL I12, H55)